Design of a thyristor-switched capacitor type voltage regulator of a self-exited induction generation - Oun, Chuan Teck. (2010)
Voltage regulators are widely used in the transmission network because it is a reliable and feasible solution for maintaining the voltage within a required voltage range. Thus, the possibilities of designing a voltage regulator controller are being investigated. This project focuses on the design of the thyristor-switched capacitor type voltage regulator controller that is commonly used in the transmission network nowadays. The project also looks into a design concept which is the simplest design, as well as the cheapest method to construct the voltage regulator controller. As the voltage regulator controller is used to maintain the generated voltage at its required range, it must be able to measure the voltage at the generator terminal, thus this project will look into the way of measuring the voltage and design of the control circuit used to control the thyristor to turn on and off. Simulation of the voltage regulator controller will be performed to obtain the main structure of the controller circuit, after which the controller is then constructed into hardware. Besides, experiment and tests will be performed on the reliability of the voltage regulator controller through a transmission network with and without the voltage regulator controller. Data obtained from the experiments and tests is then used to plot different graphs in terms of voltage generated in transmission network without controller, transmission network with controller and transmission network with controller and six loads. For the individual experiments, it will investigate the condition of the transmission network voltage and conclusion can then be drawn on whether the designed voltage regulator controller is able to maintain the voltage generated at its required range. Thus, the result can also show the feasibility and reliability of the design of voltage regulator controller in the transmission network.